Pengaruh Tingkat Pendidikan dan Pengetahuan Ibu terhadap Pemberian MP-ASI Dini di Puskesmas Cot Seumeureung, Kabupaten Aceh Barat - Pratiwi, Hernita; Iskandar, Wardah; Muliadi, Teuku; Putri, Enda Silvia (Polyscopia, 2024)
This study examines the impact of maternal education and knowledge on early complementary feeding (MP-ASI) in children aged 6-12 months at the Cot Seumeureng Health Center, Samatiga District, West Aceh Regency. Early complementary feeding, initiated before six months, can hinder optimal exclusive breastfeeding practices. This cross-sectional study involved 94 mothers of infants aged six to twelve months, with data collected through questionnaires and analyzed using the Chi Square test. Results indicate a statistically significant relationship between maternal education and early complementary feeding (p=0.001, PR=2.1), as well as between maternal knowledge and early complementary feeding (p=0.002, PR=1.8). These findings underscore the role of maternal education and knowledge in shaping early feeding practices, highlighting the importance of tailored health education programs to promote exclusive breastfeeding. The study concludes that enhanced maternal knowledge through education is crucial for improving infant feeding practices.